2011
DOI: 10.1063/1.3552992
|View full text |Cite
|
Sign up to set email alerts
|

An efficient micromixer based on multidirectional vortices due to baffles and channel curvature

Abstract: An efficient planar micromixer based on multidirectional vortices in a curved channel with radial baffles is proposed and examined in this work. The curvature of the microchannel and the radial baffles induce vortices in different directions. The multidirectional vortices and the converging-diverging flow caused by the baffles contribute together to the enhancement of mixing. The micromixer is fabricated with polydimethylsiloxane by a single planar microlithography process and the mixing behaviors are observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 20 publications
(23 reference statements)
2
92
0
Order By: Relevance
“…Electronic addresses: rykhit@hit.edu.cn and jhy_hit@hit.edu.cn. In the last decade, for better mixing efficiency, many researchers have made great effort to develop various types of passive micromixers composed of 2-D curved channel with radial baffles, 23 2-D cylindrical grooves adjoining to the main straight channel 24 and 2-D structures based on the concept of the splitting and recombination. [25][26][27][28] These micromixers did exhibit high performance at high flow rates, but at a low level the channel geometries cannot result in obvious vortices or chaotic advection and the contact surface between the streams are usually vertical without rotation and expansion, so these micromixers are not effective at lower Reynolds number unless these micromixers have a longer mixing length.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic addresses: rykhit@hit.edu.cn and jhy_hit@hit.edu.cn. In the last decade, for better mixing efficiency, many researchers have made great effort to develop various types of passive micromixers composed of 2-D curved channel with radial baffles, 23 2-D cylindrical grooves adjoining to the main straight channel 24 and 2-D structures based on the concept of the splitting and recombination. [25][26][27][28] These micromixers did exhibit high performance at high flow rates, but at a low level the channel geometries cannot result in obvious vortices or chaotic advection and the contact surface between the streams are usually vertical without rotation and expansion, so these micromixers are not effective at lower Reynolds number unless these micromixers have a longer mixing length.…”
Section: Introductionmentioning
confidence: 99%
“…In order to validate the numerical results of Newtonian fluids, the mixing index for water flowing in CSC channel without baffles was simulated and compared with previous numerical results (Tsai and Wu 2011). It can be seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Also, they compared the mixing performance of sinusoidal micromixers with results of square wave and zig-zag wave micromixers and they observed that the sinusoidal micromixer showed better mixing performance than other geometries. Tsai and Wu (2011) investigated several planar curved micromixers with radial baffles, both numerically and experimentally. They observed that the mixing efficiency improved due to the multidirectional vortices.…”
Section: Nomenclaturementioning
confidence: 99%
“…Previous researchers designed 3-D passive micromixers [21][22][23][24] to achieve a chaotic mixing effect. The mixing ratio of the serpentine microchannel is twice that obtained in a conventional straight microchannel.…”
Section: Introductionmentioning
confidence: 99%